Circumferential silicone sponge scleral buckling induced axial length changes: case series and comparison to literature - Ophir, Shira Sheen (Int J Retina Vitreous, 2017)
BACKGROUND: This study compared axial length changes induced by circumferential scleral buckling using a silicone sponge with literature reports for solid silicone rubber. METHODS: Records of patients treated with scleral buckling in 2009–2013 using a silicone sponge, with preoperative axial length biometry measurements were reviewed. Additional information included age, type of surgery, additional surgeries, phakic status and anatomical success of reattachment. Patients underwent repeat biometry. The medical literature was reviewed for articles describing axial length changes induced by circumferential buckling using solid silicone rubber. RESULTS: Twenty-eight patients (mean age 49.7 years, range 16–72) met the inclusion criteria. Mean axial length was 25.38 mm preoperatively and 26.12 mm at least 6 months postoperatively (SD 0.50 ± 0.09, p < 0.001); a mean increase of 0.74 mm. Half the patients subsequently underwent cataract surgery. Post-operative changes were not significant compared to pre-surgical refraction and corneal astigmatism. Axial length change was not significant between sexes (9 women and 19 men). CONCLUSIONS: Axial length changes induced by circumferential scleral buckling using silicone sponge exclusively are similar to those reported in the literature for solid silicone rubber buckles. Scleral buckling using a silicone sponge, which may offer several surgical advantages, induces an acceptable axial length change similar to that seen with widely-used solid silicone rubber buckles.